Knowledge, attitudes and practices about malaria among communities: Comparing epidemic and non-epidemic prone communities of Muleba district, North-western Tanzania - Kishamawe Coleman; Malima Robert; Kaatano Godfrey M; Nnko Soori E; Mwanga Joseph R; Mashauri Fabian; Kinung'hi Safari M; Magesa Stephen; Mboera Leonard EG (BMC, 2010)
Abstract Background Muleba district in North-western Tanzania has experienced malaria epidemics in recent years. Community knowledge, attitudes and practices are important in enhancing disease control interventions. This study investigated determinants of malaria epidemics in the study area in relation to household knowledge, attitudes and practice on malaria. Methods A community based cross-sectional survey involving 504 study participants was conducted between April and June 2007 using a structured questionnaire focusing on knowledge, attitudes and practices of community members in epidemic and non-epidemic villages about malaria transmission, signs and symptoms, treatment, prevention and control. Multivariate logistic regression analysis was used to assess determinants of malaria epidemics. Results A total of 504 respondents (males = 36.9%) were interviewed. Overall, 453 (90.1%) mentioned malaria as the most important disease in the area. Four hundred and sixty four respondents (92.1%) knew that malaria is transmitted through mosquito bite. A total of 436 (86.7%), 306 (60.8%) and 162 (32.1%) mentioned fever, vomiting and loss of appetite as major symptoms/signs of malaria, respectively. Of those interviewed 328 (65.1%) remembered the recent outbreak of 2006. Of the 504 respondents interviewed, 296 (58.7%) reported that their households owned at least one mosquito net. Three hundred and ninety seven respondents (78.8%) knew insecticides used to impregnate bed nets. About two thirds (63.3%) of the respondents had at least a household member who suffered from malaria during the recent epidemic. During the 2006 outbreak, 278 people (87.2%) sought treatment from health facilities while 27 (8.5%) obtained drugs from drug shops and 10 (3.1%) used local herbs. Logistic regression analysis showed that household location and level of knowledge of cause of malaria were significant predictors of a household being affected by epidemic. Conclusions Residents of Muleba district have high level of knowledge on malaria. However, this knowledge has not been fully translated into appropriate use of available malaria interventions. Our findings suggest that household location, ineffective usage of insecticide treated nets and knowledge gaps on malaria transmission, signs and symptoms, prevention and control predisposed communities in the district to malaria epidemics. It is important that health education packages are developed to address the identified knowledge gaps.